Technical performance profile of the four-time Costa Rican senior basketball league championship team - Blanco Romero, Luis (2011)
The purpose of this study was to analyze and compare the technical performance profile of the four-time Costa Rican Senior Basketball League championship team. A total of 142 games was recorded throughout the 2007, 2008 and 2009 seasons. Performance indicators selected were: two and three-point shots (converted, missed, effectiveness rates), free throws (converted, missed, effectiveness rates), points, offensive and defensive rebounds, fouls, turnovers, assists and ball steals. The information was described based on absolute and relative frequency values. Data was compared by season and by playing period based on the following non-parametric techniques: U-test, Friedman test and Chi-square. In all cases, SPSS version 15.0 was used with a significance level of p ≤ 0.05. Results showed a better profile of technical performance in the 2008 season, characterized by better percentages of two-point shots, free throws, fewer turnovers and more ball steals and assists. In relation to the playing period, the team showed a better technical performance profile during the second half of the matches. In general, the effectiveness rate of two-point shots and free throws was above 60% in both playing periods, while the three-point shot percentage ranged between 26.4% and 29.2%. In conclusion, the team showed a similar technical performance profile to that reported in the literature, as well as a clear evidence of the importance of recording and following up on technical performance indicators in basketball.